Fabryczna produkcja mebli w Krakowie od końca XIX do połowy XX wieku (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
INDUSTRIAL PRODUCTION OF FURNITURE IN CRACOW FROM THE END OF THE 19TH CENTURY TO THE MID-20TH CENTURYIn the 1880s and 1890s first factories producing construction joinery elements and furniture were established in Cracow. These were the Stanislaw Burzyhski’s Electric Carpentry Factory at 44/46 Długa Street (1887), and the Steam Flooring and Carpentry Products Plant at 14 Dajwór Street, owned by brothers Roman and Leonard Muranyi (1890). The Cracow factories production was complementary to the production of craftsmen carpenters, prevailing in Cracow over the whole period of Galician era. In the early 1920s the new plants were established, including Stanislaw Iglicki’s Furniture Factory at 12 Kolejowa Street and S. Manne’s Furniture Factory in Łagiewniki. The existing firms — S. Burzyński’s furniture factory (moved to 4 fabryczna Street) and Muranyi’s factory at 7 Pola Street, were developed. Szczepan Łojek, a businessman from Kalwaria, made an attempt to open a furniture factory in Królowej Jadwigi Street. The rapid growth of wood production and furniture factories in the early 1920s stopped in the early 1930s, during the economic crisis when most of Cracow producers of wood products and furniture closed their factories. In the late 1930s there were only two large firms operating: the Maurycy Grunberg’s UNITAS Steam Wood Products Factory and S. Manne’s Furniture Factory. Just after the end of the war, all wood processing factories were closed. The S. Manne’s factory and the Roman Muranyi’s factory were on the list of companies taken over by the state on 19 October 1946. M. Grunberg’s factory was on a similar list of November 9, 1946.In the second half of the 19th century products imported from Berlin, Dresden, Wroclaw and Vienna and cheep local production prevailed on the Cracow furniture market. In the 1920s Cracow manufacturers supplied about 20% of the total amount of furniture sold in Cracow. The production was strongly supported by local designers and artists (Cracow Workshops, the Municipal Industrial Museum carpentry workshop). However, industrial production of furniture in Cracow was rather modest from the late 19th century to the mid-20th century. That is clearly indicated by the amounts of company capital, the employment rates generally less than 100 people and the size of the plants. A chance for the development of that industry in Cracow appearing in the early 1920s was cancelled by the great economic crisis, and later by the Nazi occupation.